As construções de identidades nacionais: as óticas poéticas de Agostinho Neto e Fernando Pessoa - Silva, Lidiane Moreira e [UNESP] (2014)
Although distintic countries and literary experiences, Fernando Pessoa (1888 - 1935) and Agostinho Neto (1922 - 1979) share the theme of national identity in their respective works, Mensagem (1934) and Sagrada Esperança (1974 ). Pessoa retraces the path taken by Camões in Os Lusíadas, shedding light on myths and extolling the Portuguese nation through historical events as a way to rescue the Portuguese collective identities, while Agostinho creates a poetry marked by engagement amid a period of wars for the conquest of Angola's independence, showing how Literature holds a fundamental role for the social reconstruction of colonized peoples. Using the comparative method, the propose is a reflection on the making of poetry as a tool for dialogue and social discussion, and to promote new approaches to the poems studied, investigating similar and dissonant aspects in the poetic works and thus reflect on the relationships between colonizer and colonized